Genetic diversity and phylogeography of the elusive, but epidemiologically important Echinococcus granulosus sensu stricto genotype G3 - Kinkar, Liina; Laurimae, Teivi; Balkaya, Ibrahim; Casulli, Adriano; Zait, Houria; Irshadullah, Malik; Saarma, Urmas (Cambridge Univ Press, 2018)
Cystic echinococcosis (CE) is a severe parasitic disease caused by the species complex Echinococcus granulosus sensu lato. Human infections are most commonly associated with E. granulosus sensu stricto (s.s.), comprising genotypes G1 and G3. The objective of the current study was to provide first insight into the genetic diversity and phylogeography of genotype G3. Despite the epidemiological importance of the genotype, it has remained poorly explored due to the ambiguity in the definition of the genotype. However, it was recently demonstrated that long sequences of mitochondrial DNA (mtDNA) provide a reliable method to discriminate G1 and G3 from each other. Therefore, we sequenced near-complete mtDNA of 39 G3 samples, covering most of the known distribution range and host spectra of the genotype. The phylogenetic network revealed high genetic variation within E. granulosus s.s. G3 and while G3 is significantly less prevalent worldwide than G1, the genetic diversity of both of the genotypes is equally high. We also present the results of the Bayesian phylogeographic analysis, which yielded several well-supported diffusion routes of genotype G3 originating from Turkey and Iran, suggesting the Middle East as the origin of the genotype.
Keywords: Bayesian phylogeny; cystic echinococcosis; Echinococcus granulosus; genotype G3; genetic variability; mitochondrial genome; phylogeography; zoonoses